0
$\begingroup$

Can anyone help me with this proof.

Let $M=\{e_1, e_2, \ldots\}$ be an orthonormal subset of a Hilbert space $H$ and $A=\overline{\textrm{span}(M)}$. Show that the orthogonal projection $P:H\rightarrow A$ is given by, $$ Px=\sum_{i=1}^\infty \langle x, e_i\rangle e_i$$.

$\endgroup$
  • $\begingroup$ How did you define the projection $Px$? As the minimizer of $\|u - x\|, u \in A$? As the element such that $(Px - x, v) = 0 \quad \forall v \in A$? Maybe something else even? $\endgroup$ – user38355 Feb 12 '13 at 16:59
  • $\begingroup$ As the minimizer of $\|u-x\|$. $\endgroup$ – PtF Feb 12 '13 at 17:50
0
$\begingroup$
  • Suppose $x \in H$ and $u \in A$ are such that $$(x-u,v) = 0 \quad \forall v \in A.$$ Then for any $v \in A$ a quick calculation shows that $$\|u-x\|^2 - \|v - x\|^2 = 2(x-u,u-v) - \|u - v|^2 \le -\|u - v\|^2 \le 0$$ since $u-v \in A$. Thus $$\|u-x\|^2 \le \|v - x\|^2 \quad \forall v \in A$$ which shows that $u = Px$.

  • Now define $$u = \sum_{i=1}^\infty (x, e_i)e_i$$ Then for each $n$ the linearity and continuity of the inner product and the orthonormality of the $\{e_n\}$ yield $$(u-x, e_n) = (u,e_n) - (x,e_n) = \left(\sum_{i=1}^\infty (x,e_i)(e_i, e_n)\right) - (x, e_n)$$ $$ = (x,e_n)(e_n, e_n) - (x,e_n) = (x,e_n) - (x,e_n) = 0.$$ Invoking continuity and linearity of the inner product again, this shows that $$(u-x,v) = 0 \quad \forall v \in A$$ since $A = \overline{\mbox{span } \{e_n\}}$.

  • Combining the first two points shows that in fact $$Px = \sum_{i = 1}^\infty (x,e_i)e_i$$ as desired.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.